Phyto-Mediated Synthesis of Porous Titanium Dioxide Nanoparticles From Withania somnifera Root Extract: Broad-Spectrum Attenuation of Biofilm and Cytotoxic Properties Against HepG2 Cell Lines - Al-Shabib, Nasser A.; Husain, Fohad Mabood; Qais, Faizan Abul; Ahmad, Naushad; Khan, Altaf; Alyousef, Abdullah A.; Arshad, Mohammed; Noor, Saba; Khan, Javed Masood; Alam, Pravej; Albalawi, Thamer H.; Shahzad, Syed Ali (Frontiers in Microbiology, 2020)
There is grave necessity to counter the menace of drug-resistant biofilms of pathogens using nanomaterials. Moreover, we need to produce nanoparticles (NPs) using inexpensive clean biological approaches that demonstrate broad-spectrum inhibition of microbial biofilms and cytotoxicity against HepG2 cell lines. In the current research work, titanium dioxide (TiO2) NPs were fabricated through an environmentally friendly green process using the root extract of Withania somnifera as the stabilizing and reducing agent to examine its antibiofilm and anticancer potential. Further, X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscopy (SEM), transmission electron micrograph (TEM), energy-dispersive X-ray spectroscopy (EDS), dynamic light scattering (DLS), thermogravimetric analysis (TGA), and Brunauer-Emmett-Teller (BET) techniques were used for determining the crystallinity, functional groups involved, shape, size, thermal behavior, surface area, and porosity measurement, respectively, of the synthesized TiO2 NPs. Antimicrobial potential of the TiO2 NPs was determined by evaluating the minimum inhibitory concentration (MIC) against Escherichia coli, Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, Listeria monocytogenes, Serratia marcescens, and Candida albicans. Furthermore, at levels below the MIC (0.5 × MIC), TiO2 NPs demonstrated significant inhibition of biofilm formation (43–71%) and mature biofilms (24–64%) in all test pathogens. Cell death due to enhanced reactive oxygen species (ROS) production could be responsible for the impaired biofilm production in TiO2 NP–treated pathogens. The synthesized NPs induced considerable reduction in the viability of HepG2 in vitro and could prove effective in controlling liver cancer. In summary, the green synthesized TiO2 NPs demonstrate multifarious biological properties and could be used as an anti-infective agent to treat biofilm-based infections and cancer.